2019
DOI: 10.1038/s41556-019-0392-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional transcription promoters at DNA double-strand breaks mediate RNA-driven phase separation of damage-response factors

Abstract: Damage-induced long non-coding RNAs (dilncRNA) synthesized at DNA double-strand breaks (DSBs) by RNA polymerase II (RNAPII) are necessary for DNA damage response (DDR) foci formation. We demonstrate that induction of DSBs results in the assembly of functional promoters that include a complete RNAPII pre-initiation complex (PIC), MED1 and CDK9. Absence or inactivation of these factors causes DDR foci reduction both in vivo and in an in vitro system that reconstitutes DDR events on nucleosomes. We also show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
260
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(285 citation statements)
references
References 86 publications
(81 reference statements)
25
260
0
Order By: Relevance
“…53BP1 requires its oligomerization domain for recruitment to sites of DNA damage and shows hallmarks of dynamic self-assembly by phase separation [25][26][27] . A reduced concentration of H4K20me2, as present in replicated nascent chromatin, therefore likely increases the threshold for efficient 53BP1 accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…53BP1 requires its oligomerization domain for recruitment to sites of DNA damage and shows hallmarks of dynamic self-assembly by phase separation [25][26][27] . A reduced concentration of H4K20me2, as present in replicated nascent chromatin, therefore likely increases the threshold for efficient 53BP1 accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…In this case it might prevent hybridization of putative exposed single stranded DNA with RNA, thus facilitating alternative end joining pathways. Interestingly, the initial formation of 53BP1 foci has been described to require the recruitment of RNA polymerase II and transcription of long non-coding DNA in the vicinity of a DSB [49][50][51] and processing them into small non-coding DNA-damage response RNA (DDRNA, reviewed in [52]). Although the evidence of these processes after high-LET irradiation have not yet been presented, such transcriptional activity is fully compatible with the open EC-l DNA organization within DNA damage domains.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the well documented inhibition of transcription reported above, recent studies have revealed that de novo transcription occurs at free DNA ends in a process that generates non‐polyadenylated damage‐induced long non‐coding RNAs (dilncRNAs). [ 19–23 ] DilncRNAs were identified using strand specific RT‐qPCR (ssRT‐qPCR) and were postulated to be the precursors of damage‐induced small RNAs (diRNAs). [ 19,20,22,24 ] Production of dilncRNAs is sensitive to RNAPII inhibitors, but not to inhibitors specific to other RNA polymerases.…”
Section: De Novo Rna Synthesis At Dsbs: An Unexpected Discoverymentioning
confidence: 99%
“…[ 25 ] Moreover, the MRN complex is involved in the assembly of a transcription pre‐initiation complex at DSBs. [ 23 ] Despite these recent observations, the specifics of the initiation mechanism are not well understood. Interestingly, a detailed RNA analysis using deep sequencing revealed that dilncRNAs emerge only a few nucleotides away from the break site.…”
Section: De Novo Rna Synthesis At Dsbs: An Unexpected Discoverymentioning
confidence: 99%